1985
DOI: 10.2135/cropsci1985.0011183x002500040018x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Etched Seed Coats and Environmental Conditions on Soybean Seed Quality1

Abstract: Environmental factors prevalent during the growing season in Kansas frequently result in soybean ([Glycine max (L.) Merr.] seed with a high incidence of seed‐coat etching. This seed‐coat condition has been associated with seedlots which have low germination and vigor ratings. However, seedlots free of any seedcoat etching have also exhibited low levels of germination and vigor. Since the impact etching had on the performance of a soybean seedlot was unclear, this study was conducted to examine the effect of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…First, SCC spoils the appearance of soybean seed and sometimes affects bean curd (tofu) yield and quality (Hou and Chang 1998), thereby causing price decline. Second, SCC affects the germination and vigor of seed (Burchett et al 1985, Thomison et al 1989. Soybean SCC rate varies with both environmental conditions and the genetic background of the cultivar (Burchett et al 1985, Okabe 1996.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, SCC spoils the appearance of soybean seed and sometimes affects bean curd (tofu) yield and quality (Hou and Chang 1998), thereby causing price decline. Second, SCC affects the germination and vigor of seed (Burchett et al 1985, Thomison et al 1989. Soybean SCC rate varies with both environmental conditions and the genetic background of the cultivar (Burchett et al 1985, Okabe 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Second, SCC affects the germination and vigor of seed (Burchett et al 1985, Thomison et al 1989. Soybean SCC rate varies with both environmental conditions and the genetic background of the cultivar (Burchett et al 1985, Okabe 1996. As cultivation methods to avoid cracking have not been established, genetic improvement to reduce SCC is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation did not influence the incidence of seed coat etching but increased germination by 2% (Burchett et al, 1985). In this study, Burchett et al (1985) failed to identify the environmental conditions that caused seed-coat etching.…”
Section: Production Of Etched Seed Coatmentioning
confidence: 69%
“…High seed coat etching resulted in lower seed germination (Burchett et al 1985). Burchett et al (1985) found that etched coat seeds had lower warm germination by about 18% across years, locations, and genotypes. Etched seeds, with low moisture content (8%),…”
Section: Production Of Etched Seed Coatmentioning
confidence: 99%